Romantic Labouring-Class Pastoral as Eco-Queer Camp - Keegan, Bridget (Romanticism on the Net)

(untitled) (Université de Montréal, 2004)
AbstractThe few eighteenth-century and Romantic labouring-class poems that have been recuperated within recent efforts at canon revision appear to have attracted critical attention primarily because they represent the authentic hardships of the working poor, thereby suggesting a nascent effort toward solidarity. However, while these direct expressions of a more familiarly class-based politics are important, they are also relatively rare within the broader tradition of labouring-class poetry, a tradition made up of countless poems written by over 1300 poets who published in Great Britain and Ireland between 1700 and 1900. This essay proposes that a queer reading might productively undermine the usual critical practices for evaluating and valorizing labouring-class writing. It begins by questioning the current logic for determining whether to include a labouring-class poet within mainstream literary history, a logic which proceeds from the assumption that, as John Guillory describes, “the noncanonical author’s experience as a marginalized social identity necessarily reasserts the transparency of the text to the experience it represents” (Cultural Capital 10). A queer reading complicates such representational reductionism. Furthermore, it may also contribute to a broader queer history of eighteenth-century and Romantic literature, which although it has certainly been sensitive to the class issues, has heretofore focused predominantly on tensions between bourgeois and aristocratic subjects. The essay focuses in particular on conventional pastoral poetry as a paradoxically felicitous site from which to launch a queer reading of labouring-class poetry. Through Moe Meyer’s concept of queer camp, the essay explores what happens when labouring-class pastoral is read as queer camp expression. Through a close reading of poems by John Clare, Janet Little and Samuel Thomson, the essay also considers to what extent these poems question representations of what is “natural” for a particular rank of society and, more broadly, opens up the discussion of what is “natural” in other categories of identity, including sexuality.